Performance-enhancing drugs, fair competition, and Olympic sport - Catlin, D. H.; Murray, T. H. (Journal of the American Medical Association, 1996)
Drug control has become an important component of Olympic sport. At the Atlanta Centennial Olympic Games, urine samples will be tested for prohibited substances, including stimulants, narcotics, anabolic agents, diuretics, peptides, and glycoprotein hormones as well as prohibited methods of enhancing performance, including blood doping and pharmacological, chemical, and physical manipulation of the urine. Drug testing programs must address short-acting stimulants, beta-blockers, and diuretics; training drugs such as anabolic steroids; and drugs affecting the detectability of other drugs. Programs include short- or no-notice testing during training periods, testing at qualifying competitions, and testing at the Olympic Games. Procedures and disposition that occur when a prohibited substance is found in an athlete competing in an Olympic sport are discussed. An analysis of the ethics of the use of performance-enhancing drugs in sports and of drug control in terms of fair competition and the impact of enhancement technologies of the meaning of sports also is presented.